How Travel Influencer and Social Media Influence Tourist Travel Decision to Ubud - Rahjasa, Surya Laksana; Prasasti, Galih; Apriliani, Khofifah Malika (Jurnal Penelitian Pariwisata, 2024)
Bali is a popular tourist destination, with 522,141 foreign tourists visiting the island directly in August 2023. Ubud, is renowned for its natural beauty, arts and culture, and authentic village life. This sub-district has a total area of 42.38 km2 and is included in the top five most favorite cities in the world according to Travel and Leisure. The rapid development of tourism in Ubud has led to an increase in the number of influencers promoting on social media, giving rise to the 'Travel Envy' phenomenon. The impact of travel influencers in influencing travel decisions is important to study of how important the role of travel influencers is. The researchers aimed to discuss the impact of social media content created by travel influencers on tourists' decision-making and travel behavior. This research used a qualitative research method that conducted interviews with 17 individuals aged 19-35 years, respondents from various regions and countries who had traveled to Ubud. Research shows that tourists tend to rely on social media reviews and recommendations from travel influencers when planning their trip to Ubud. They are more likely to be interested in content related to travel destinations announced by travel influencers they follow. We found that social media and travel influencers can influence people's travel decisions. Keywords: travel influencers, social media, travel decision